Decoding Organic Food Buying Intention: The Interplay of Health Consciousness and Perceived Value Among Urban Consumers in Malang - Napitupulu, Simon Azriel; Setiawan, Budi; Rayesa, Neza; Haryati, Novi; Rohman, Ach. Ainur (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
This study investigates the role of health consciousness and consumer perceived value (CPV) in shaping organic food purchase intentions among urban consumers in Malang City, Indonesia. Amid rising health awareness and growing demand for organic products, this research explores how functional, emotional, economic, and social value dimensions mediate the link between health consciousness and purchasing intention. A quantitative approach was employed, gathering data from 90 purposively sampled individuals with prior organic food purchasing experience. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings reveal that while health consciousness does not directly influence purchase intention, it significantly enhances perceptions of functional, emotional, and economic value. Among CPV dimensions, functional and economic values have the strongest positive impact on purchase intention, whereas emotional value shows no significant effect, and social value is found to be insignificant. These results highlight that consumers primarily pursue organic food for utilitarian benefits related to health safety, reliability, and cost-effectiveness rather than for social recognition or emotional gratification. The study underscores the importance of targeted marketing strategies that emphasize tangible product benefits and consumer education to boost organic food consumption. Implications include the need for policy support and certification transparency to bridge gaps between health awareness and sustainable consumption behavior. This research contributes to the literature by clarifying the indirect pathways through which health consciousness influences purchase decisions via CPV constructs.